Controlling the Assembly of PdII/Bianthryl‐Based Monomeric and Dimeric Interlocked Cages by Steric Effects - Sota Watanabe; Dr. Masahiro Yamashina; Dr. Eiji Tsurumaki; Prof. Dr. Shinji Toyota (ChemistryEurope, 2023)
Abstract In the energy landscape of coordination‐driven self‐assembly processes, the isolation of kinetically formed supramolecular cages has long been identified as a challenging task. This study reports a reliable strategy for the selective isolation of kinetically or thermodynamically preferred stable coordination cages, whose formation depends on the degree of steric protection offered by the exterior side chains. The combination of PdII ions with arc‐shaped 2,2′‐bianthryl‐based ligands that contain different numbers of methoxyethoxy side chains led to the quantitative formation of both kinetically favorable monomeric M2L4 cages and thermodynamically favorable dimeric (M2L4)2 interlocked cages. These assemblies were structurally fully characterized via NMR spectroscopy, mass spectrometry, and single‐crystal X‐ray diffraction analysis. Although the monomeric cages with fewer exterior side chains can reassemble into interlocked cages, the cages with more exterior substituents remain monomeric cages under similar conditions. A computational study revealed that this different behavior is mainly governed by the destabilization of the interlocking assemblies due to the steric repulsion among the side chains on the overcrowded exterior. Furthermore, the kinetically stabilized monomeric M2L4 cages exhibit permanent host abilities toward sulfonate guests, while the cages with lower steric protection undergo dimerization accompanied by guest release.